Antifungal activity of dimethyl sulfoxide against Botrytis cinerea and phytotoxicity on tomato and lettuce plants. (3rd July 2020) - Petruccelli, V.; Brasili, E.; Varone, L.; Valletta, A.; Pasqua, G.
Abstract: For the first time the antifungal activity of dimethyl sulfoxide (DMSO) was evaluated against Botrytis cinerea, that it is one of the phytopathogenic fungi which causes the greatest damage in agriculture. In in-vitro tests, the greatest inhibitory effect of DMSO on fungal grow was recorded at pH 6. A significant growth inhibition was caused by 0.5% DMSO at 96 h post-inoculation. With higher DMSO concentrations, significant effects were recorded starting from 48 h post-inoculation. As the medium pH decreased, the inhibitory effect of DMSO also decreased. At pH 4 and 5 significant growth inhibition was caused by 1% DMSO starting from 72 h post-inoculation. At all tested pH values, a total growth inhibition was caused by ≥ 2% DMSO. On tomato leaves infected with B. cinerea, 2% DMSO significantly decreased the extent of damaged leaf area. The administration of DMSO at concentrations ranging from 0.5 to 2% through nebulization on leaves of young Solanum lycopersicum and Lactuca sativa plants did not change the chlorophyll fluorescence (Fv/Fm and ΦPSII ) at any of the experimental times. Overall, the data obtained suggest that, at the concentrations tested, DMSO is toxic to B. cinerea, while it is well tolerated by lettuce and tomato plants.